2022
DOI: 10.3389/fpsyg.2022.859577
|View full text |Cite
|
Sign up to set email alerts
|

I am one of you! Team prototypicality as a facilitator for female leaders

Abstract: In the present study, we complement role congruity theory with insights from the Social Identity Model of Leadership. We propose that especially female leaders benefit from team prototypicality, i.e., being representative of the group they are leading. We assume that team prototypicality shifts the comparative frame away from higher-order categories like gender and leader roles to more concrete team-related properties and thereby reduces disadvantages for female leader that stem from the incongruity between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…For women in leadership, this has could result in evaluations of their leadership abilities as lacking, simply based on the idea that they should not be or 132 cannot be good leaders. Bark et al (2022) used role congruity theory to consider the idea of prototypicality, meaning that a leader is representative of the group they oversee, and leadership evaluation. They found that perception of role incongruity is lessened when a female leader is seen as an archetype of the group.…”
Section: Equity In Leadership Evaluationsmentioning
confidence: 99%
“…For women in leadership, this has could result in evaluations of their leadership abilities as lacking, simply based on the idea that they should not be or 132 cannot be good leaders. Bark et al (2022) used role congruity theory to consider the idea of prototypicality, meaning that a leader is representative of the group they oversee, and leadership evaluation. They found that perception of role incongruity is lessened when a female leader is seen as an archetype of the group.…”
Section: Equity In Leadership Evaluationsmentioning
confidence: 99%